Externalities and Growth Accounting - Benhabib, Jess; Jovanovic, Boyan (American Economic Review, 1991)
This paper tackles two puzzles: the high empirical elasticity of aggregate output with respect to the measured capital input and the seemingly high variability of growth rates over countries in the medium run. We find that one need not invoke increasing returns or externalities to capital to explain these two puzzles. Rather, they are consistent with a constant-returns-to-scale aggregate production function, so long as the exogenous Solow residual process has enough persistence in it. In our model, casuality runs exclusively from knowledge to capital, and therefore the apparent absence of an external effect to the capital input says nothing about the importance of spillovers in the creation of knowledge.